SLUPI IN DOGS OF MEXICO CITY - BARROETA FLORES, L (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
By means of diazotization of the 6-methoxy-8-amino-quinoline and combination with stovarsol in an alkaline medium an azo dye was obtained which is inactive as an antimalarial and which does not give a chloranil reaction
CIENC MEX
Keywords: SLUPI, DOGS, MEXICO CITY; MULTIDISCIPLINARIA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL